2018
DOI: 10.1007/jhep04(2018)091
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of a light sterile neutrino in T2HK

Abstract: We investigate the performance of T2HK in the presence of a light eV scale sterile neutrino. We study in detail its influence in resolving fundamental issues like mass hierarchy, CP-violation (CPV) induced by the standard CP-phase δ 13 and new CP-phase δ 14 , and the octant ambiguity of θ 23 . We show for the first time in detail that due to the impressive energy reconstruction capabilities of T2HK, the available spectral information plays an important role to enhance the mass hierarchy discovery reach of this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 93 publications
2
26
1
Order By: Relevance
“…The centroids of the two ellipses basically coincide, hence it is clear that the setup cannot discriminate the MH. This is qualitatively different with respect to what occurs in other LBL experiments (T2HK [27] and especially DUNE [22]), where the two ellipses get separated due to the presence of the matter effects. In the 3+1 scheme, two CP phases are present and their variation in the range [−π, π] gives even more freedom.…”
Section: Mass Ordering and θ 23 Octant Sensitivity In The 4-flavor Sccontrasting
confidence: 96%
See 3 more Smart Citations
“…The centroids of the two ellipses basically coincide, hence it is clear that the setup cannot discriminate the MH. This is qualitatively different with respect to what occurs in other LBL experiments (T2HK [27] and especially DUNE [22]), where the two ellipses get separated due to the presence of the matter effects. In the 3+1 scheme, two CP phases are present and their variation in the range [−π, π] gives even more freedom.…”
Section: Mass Ordering and θ 23 Octant Sensitivity In The 4-flavor Sccontrasting
confidence: 96%
“…In this paper, we focus on the proposed super beam experiment to be performed at the European Spallation Source (ESSνSB), where a very powerful neutrino beam will be shot over a distance of about 540 km. Our present study is complementary to other recent investigations performed about DUNE [19][20][21][22][23][24][25], T2HK [25][26][27], and T2HKK [25,28]. Other studies on the impact of light sterile neutrinos in LBL setups can be found in [29][30][31][32][33][34][35][36][37].…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…It has also been shown that this new phase from the seesaw mechanism brings in a new degeneracy that leads to an important ambiguity in extracting the "standard" three-neutrino phase δ CP [18]. Similar ambiguities in the determination of the oscillation parameters can also appear when considering the possibility of having light sterile neutrinos [19,20]. We discuss the potential of our proposed experimental setup for probing this scenario as well.…”
Section: Introductionmentioning
confidence: 83%